A practical method for predicting post-flutter behavior of a rectangular section. Issue 216 (September 2021) - Zhang, Ruilin; Liu, Zhiwen; Wang, Lianhua; Chen, Zhengqing
Abstract: In this study, a practical method is proposed to predict the two-degree-of-freedom (2DOF) post-flutter behavior of a 5:1 rectangular section. For this method, a hybrid strategy in the time–frequency domain is introduced to obtain the time-history solution of the nonlinear coupled oscillator, and the nonlinear unsteady aerodynamic forces, described by the amplitude-dependent flutter derivatives, are considered as well as the other nonlinearities of the section model system, i.e., damping and stiffness. Moreover, wind tunnel tests are performed to validate the effectiveness of the proposed method. The numerical results show that the system may exhibit limit cycle oscillation (LCO) due to the aerodynamic and/or damping nonlinearities. Finally, this method is applied to predict the aeroelasticity of a continuum model and to analyse the parameter sensitivity. Highlights: A method is proposed to predict the post-flutter behavior of a rectangular section. The effects of the system's nonlinearity on the post-flutter behavior are revealed. The post-flutter analysis is performed considering the 3D aeroelastic effects.